The effect of subclinical hypothyroidism on platelet parameters - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2009)
Background: Hypothyroidism has a broad clinical spectrum. Today, physicians frequently encounter patients with very mild thyroid dysfunction instead of overt hypothyroidism. These patients have normal serum levels of thyroxine and triiodothyronine and only mildly elevated serum thyrotropin levels. Such patients are often identified through routine screening or in the course of an evaluation of common nonspecific symptoms. On the other hand, coronary heart disease is the leading cause of death in developed countries. There are studies, which suggest platelets play a role in the pathogenesis of atherosclerosis and coronary heart disease. Aim: The aim of this study is to compare the platelet count and other platelet parameters in subclinical hypothyroidic and euthyroidic healthy control group and to investigate whether these parameters have a predictive significance in patients with subclinical hypothyroidism. Materials and methods: Forty-seven patients with subclinical hypothyroidism and 30 euthyroidic healthy control group were enrolled into the study. Results: Patients with subclinical hypothyroidism had higher mean platelet volume (MPV) and platelet distribution width (PDW) values than control group, which were statistically significant (p<0.001 and p<0.001), respectively. Conclusion: Our results indicate that MPV and PDW play an important predictive role in subclinical hypothyroidism.
Keywords: Subclinical hypothyroidism; platelets; mean platelet volume; INDEPENDENT RISK-FACTOR; SMALL-SIZED PLATELETS; MYOCARDIAL-INFARCTION; VOLUME